2020
DOI: 10.1055/s-0039-3400247
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles as Imaging and Therapeutic Agents for Atherosclerosis

Abstract: Atherosclerosis is the major cause of cardiovascular diseases and is the leading cause of mortality worldwide. Iron oxide nanoparticles have emerged as potential diagnostic and therapeutic agents for a wide range of conditions. To date, the theranostic applications of iron oxide nanoparticles have been studied mainly in cancer, but atherosclerosis has not received the same attention. Therefore, it appears appropriate to review the current and future applications of iron oxide nanoparticles for the diagnosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…However, it is important to acknowledge the current limitations of contrast agents, including extended scanning times, rapid clearance through the kidneys, and potential toxicity. 116 Hydrodentical has enhanced gadolinium chelates (gadolinium chelates are the most common CAs in clinical MRI). The relaxation measurement properties of the study showed that this can enhance the relaxation ability of CAs by a factor of 12 by forming a complex equilibrium between polymer chain elastodynamics and water osmotic pressure.…”
Section: Nanoparticles For Diagnostic Imagingmentioning
confidence: 99%
“…However, it is important to acknowledge the current limitations of contrast agents, including extended scanning times, rapid clearance through the kidneys, and potential toxicity. 116 Hydrodentical has enhanced gadolinium chelates (gadolinium chelates are the most common CAs in clinical MRI). The relaxation measurement properties of the study showed that this can enhance the relaxation ability of CAs by a factor of 12 by forming a complex equilibrium between polymer chain elastodynamics and water osmotic pressure.…”
Section: Nanoparticles For Diagnostic Imagingmentioning
confidence: 99%
“…To achieve the specific targeting of the characteristics that are correlated with plaque vulnerability, functionalized nanoparticles are prepared and modified with ligands that show specific binding to overexpression biomarkers. [ 74 ] In the vulnerable plaque microenvironment, a number of targets, such as overactivation of cells, overexpression of surface molecules, oversecretion of enzymes or cytokines, and neovascularization, have been exploited to design molecular imaging probes for visualizing the vulnerability of atherosclerotic plaques. Based on the perspective of vulnerable plaque composition, we summarized specific biomarkers that have been employed for active targeting imaging as follows: a) monocytes/macrophages; b) foam cells; c) inflammatory components; d) neovascularization; and e) extracellular matrix (see Table 1 ).…”
Section: Targeting Strategies For the Imaging Of Vulnerable Atheroscl...mentioning
confidence: 99%
“…To achieve the specific targeting of the characteristics that are correlated with plaque vulnerability, functionalized nanoparticles are prepared and modified with ligands that show specific binding to overexpression biomarkers. [74] In the vulnerable plaque microenvironment, a number of targets, such as overactivation of cells, overexpression of surface molecules, oversecretion of enzymes or cytokines, and neovascularization, have been exploited to design molecular imaging probes for Adv. Mater.…”
Section: Active Targetingmentioning
confidence: 99%
“…These new approaches are increasingly based on molecular understanding of the disease, allowing specific nanomedicine-based molecular imaging and therapy [ 121 , 122 , 123 , 124 , 125 , 126 ]. Of particular interest are IONPs that can be used as transport vehicles for diagnostic or therapeutic agents through specific surface coating and functionalization, thus enabling site-specific and targeted delivery [ 127 , 128 , 129 , 130 ]. Meanwhile, there are numerous studies on NP-based imaging of plaques [ 131 , 132 ].…”
Section: Cardiovascular Tissue Regeneration and Engineeringmentioning
confidence: 99%